2006
DOI: 10.1097/01.mnh.0000247493.70129.91
|View full text |Cite
|
Sign up to set email alerts
|

The economics and ethics of kidney transplantation: perspectives in 2006

Abstract: Given the rising demand for kidney transplantation within a setting of scarce resources, the economic and ethical dimensions of transplant medicine are of increasing interest to patients, providers, and payers. Research in these areas will help uncover ways to utilize this important medical technology in the most ethical and cost-effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It will be necessary to look for more causes of this situation and, above all, for there to be clear political and institutional support for this type of therapy [19]. This is especially now when living kidney donation has significantly better results than cadaveric donation, and therefore it is a clear option for complementing cadaveric kidney donation, and even as a first line treatment choice [20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…It will be necessary to look for more causes of this situation and, above all, for there to be clear political and institutional support for this type of therapy [19]. This is especially now when living kidney donation has significantly better results than cadaveric donation, and therefore it is a clear option for complementing cadaveric kidney donation, and even as a first line treatment choice [20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…17 Nonetheless, it was indicated that given the rising demand for kidney transplantation within a setting of scarce resources, the economic and ethical dimensions of transplant medicine are of emerging interest to patients, providers, and payers. 18,19 Equally important, but reported not to be clear yet in many contexts, is the question of obtaining organs and the level as well as the appropriateness of incentives to donors. 20 In Ethiopia, the first national kidney transplantation center was opened at Saint Paul's Hospital Millennium Medical College (SPHMMC) in September 2015 in collaboration between the ministry of health and the medical faculty at the University of Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…17 Nonetheless, it was indicated that given the rising demand for kidney transplantation within a setting of scarce resources, the economic and ethical dimensions of transplant medicine are of emerging interest to patients, providers, and payers. 18,19 Equally important, but reported not to be clear yet in many contexts, is the question of obtaining organs and the level as well as the appropriateness of incentives to donors. 20…”
Section: Introductionmentioning
confidence: 99%
“…To a recipient in the waiting list 3. To a designated recipient (Kim et al, 2006) There should be no pressure on the donor in terms of ethics. As mentioned in the literature, 'personal willingness' may not be the only reason in indirect donations and requires detailed investigation.…”
Section: Main Components Of Altruismmentioning
confidence: 99%
“…Given the studies about organ and tissue transplants, we note that organ donations from related or unrelated living donors have become more widespread due to increasing need for organs. (Lennerling & Nyberg, 2004;Kim et al, 2006, Donelly et al, 1999, Mousavi, 2006, Al-Khader, 2005. Unfortunately, these sources have so far been unable to keep up with the demand.…”
Section: Introductionmentioning
confidence: 99%